Solubility and thermodynamic analysis of aceclofenac in different {Carbitol + water} mixtures at various temperatures - Faiyaz Shakeel; Ramadan Al-Shdefat; Mohammad A. Altamimi; Usama Ahmad (BMC Chemistry, 2024)
Abstract The solubility and thermodynamic properties of the anti-inflammatory drug aceclofenace (ACF) have been assessed in a range of {2-(2-ethoxyethoxy)ethanol (Carbitol) + water} combinations at temperatures ranging from 298.2 K to 318.2 K and atmospheric pressure of 101.1 kPa. The shake flask method was employed to determine the solubility of ACF, and various models including “van’t Hoff, Apelblat, Buchowski-Ksiazczak λh, Yalkowsky-Roseman, Jouyban-Acree, and Jouyban-Acree-van’t Hoff models” were used to validate the results. The computational models demonstrated a strong correlation with the experimental ACF solubility data, as indicated by the error values of < 3.0%. In the compositions of {Carbitol + water}, the ACF mole fraction solubility was enhanced by temperature and Carbitol mass fraction. The solubility of ACF in mole fraction was found to be lowest in pure water (1.07 × 10− 6 at 298.2 K), and highest in pure Carbitol (1.04 × 10− 1 at 318.2 K). Based on the positive values of the calculated thermodynamic parameters, the dissolution of ACF was determined to be “endothermic and entropy-driven” in all of the {Carbitol + water} solutions that were studied. It was also observed that enthalpy controls the solvation of ACF in solutions containing {Carbitol + water}. ACF-Carbitol had the strongest molecular interactions in contrast to ACF-water. Based on the results of this study, Carbitol holds significant potential for enhancing the solubility of ACF in water.